Tracing the emergence of drowning prevention on the global health and development agenda: a policy analysis. Issue 7 (July 2022) - Scarr, Justin-Paul; Buse, Kent; Norton, Robyn; Meddings, David R; Jagnoor, Jagnoor
Summary: Drowning has been a neglected health issue, largely absent from the global health and development discourse, until the UN General Assembly adopted its first resolution on global drowning prevention in 2021. This policy analysis examines the role of issue characteristics, actor power, ideas, and political contexts in the emergence of drowning prevention, and it also identifies opportunities for future actions. We identified three factors crucial to enhancing prioritisation: (1) methodological advancements in population-representative data and evidence for effective interventions; (2) reframing drowning prevention in health and sustainable development terms with an elevated focus on high burdens in low-income and middle-income contexts; and (3) political advocacy by a small coalition. Ensuring that the UN resolution on global drowning prevention is a catalyst for action requires positioning of drowning prevention within global health and sustainable development agendas; strengthening of capacity for multisectoral action; expansion of research measuring burden and identifying solutions in diverse contexts; and incorporation of inclusive global governance, commitments, and mechanisms that hold stakeholders to account.